Framing Detik.com vs Kompas.com in the International Tourism Tragedy on Mount Rinjani - Maharani, Cintya Putri; Rahmawati, Laili Etika (Universitas Muhammadiyah Surakarta, 2025)
The mass media plays an important role in shaping public perceptions of tourism crises, especially whenthe tragedy involves foreign tourists and has the potential to affect a country's international image. Thisstudy aims to analyze and compare the framing patterns of Detik.com and Kompas.com in reporting thetragedy of the fall of a Brazilian tourist, Juliana Marins, on Mount Rinjani. The urgency of this study liesin the still limited comparative studies of Indonesian media framing in cases of tourism crises that havea global impact, whereas media construction in situations like this can influence internationalperceptions of Indonesia's ability to handle adventure tourism. This study uses a qualitative approachwith a content analysis method based on Robert N. Entman's framing model. The results show thatDetik.com tends to frame the tragedy in the context of digital diplomatic conflict and netizen emotionalstress, while Kompas.com emphasizes the dimensions of safety, evacuation procedures, andinstitutional reflection. These differences are influenced by the editorial orientation, audiencesegmentation, and journalism style of each media. This study contributes to the development of mediaframing studies and offers practical implications for crisis communication and more responsiblejournalism in the digital era.